A study on cutting errors in the tooth profiles of the spur gears manufactured in CNC milling machine - Ozel, Cihan (Springer London Ltd, 2012)
In this study, the cutting errors in the tooth profile of the spur gears which are manufactured by end mill according to radial cutting method in three-axis CNC milling machine are investigated. According to this method, a mathematical approach in order to investigate the cutting errors of the tooth profile is presented. Then, mathematical expressions determining the error quantity in the tooth profile curve are derived by using this approach, and a programme is developed in the MATLAB. Parameters such as module (m), tooth number (N), pressure angle (a...) and cutting angle (alpha (m) ) in the programme are changed, and the cutting errors of the involute tooth profile according to the obtained results are interpreted graphically. As a result, it is seen that the cutting errors in the involute curve increase according to increments of m, N, a... and alpha (m) .
Keywords: The spur gear; End mill; CNC milling machine; Cutting errors